Screening of Optimal Phytoconstituents through In silico Docking, Toxicity, Pharmacokinetic, and Molecular Dynamics Approach for Fighting against Polycystic Ovarian Syndrome - Narayanan, Pavithra Lakshmi; Vellapandian, Chitra (Current Pharmaceutical Design, 2025)
BackgroundPolycystic ovarian syndrome (PCOS) is a hormonal disorder caused by excessive secretion of male sex hormones in females. Herbal remedies for PCOS are lightning up as they bypass the adverse effects and are profoundly safe on prolonged usage.ObjectiveThe present study included a selection of 34 herbs pursuing biological effects on the uterus, and their major chemical constituents were subjected to a series of in silico techniques using different software. The proteins contributing majorly to the hormonal functions like human cytochrome P450 CYP17A1 (3RUK), progesterone (1E3K), and estrogen receptor (1X7R) were selected for the study.MethodsMolecular docking studies were performed using AutoDock 1.5.7. The pharmacokinetic properties were predicted using the SwissADME online tool, while toxicity parameters were assessed with OSIRIS toxicity explorer and pkCSM. Molecular dynamics simulations and free energy calculations were performed using the Schrödinger suite.ResultsConstituents with a basic steroidal nucleus demonstrated high binding energy values. An analysis of all the in silico techniques showed that Sarsasapogenin from Asparagus racemosus exhibited strong binding energies of -10.88 kcal/mol, -10.51 kcal/mol, and -9.79 kcal/mol with the selected specific proteins. In molecular dynamics simulations, Sarsasapogenin displayed ideal stability, with RMSD fluctuations below 3 Å and RMSF slightly higher than the corresponding peak of apoprotein. Additionally, it showed a favorable drug-likeness profile and non-toxic effects across all screened parameters.ConclusionFrom the list of the selected constituents, Sarsasapogenin was found to be ideal, and further research on it for targeting PCOS is expected to yield promising results.
Keywords: hormonal disorder